Mjesto Satira u hrvatskoj epici i književnoj kulturi 18. stoljeća - Fališevac, Dunja (2000)
The position of Satyr in Croatian epic writing and in 18th century literary culture
The article determines and classifies the body of narrative epic works of Croatian 18th century literature. Furthermore, it analyses the Satyr from the standpoint of a contemporary Weltanschauung, and of historic mentality and antropological enlightenment concepts in particular. The article tries to point toward the beginnings of the new image of man and world formed by the contents of Satyr and stress the importance of the work's innovative components for Croatian culture
Projekt MZOS
HRV